Semi-charmed life - Third Eye Blind; Jenkins, Stephan; Elektra Entertainment Group (New York : Elektra Entertainment Group, 1997)
Contains two versions of the pop rock single.
CD 1 : Radio edit / (3:45) -- Original version / (4:27).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music; Songs, English